Novas matrizes míticas em O turista aprendiz de Mário de Andrade e em Tristes trópicos de Claude Lévi-Strauss - Gonçalves, Sandra Maria Luvizutto (2010)
The objective of this paper is to develop a comparison study between cultural and artistic experiences narrated by the poet Mário Raul de Moraes Andrade in O turista aprendiz (2002) and Tristes trópicos (1996) by the French anthropologist and writer Claude Lévi-Strauss. The impressions captured by them while visiting the Amazon region are our study and demonstration objects, sustained by the concepts of alterity, based on the exotic eye and the encounter with the Other . The central objective is in the reading and analysis of the travel reports, which confirmed the experience lived by the writers, showing that both of them trespassed the physical geography of visited places and, literarily, reconfigured it by means of artistic and poetic subjectivity in order to be able to unveil the new mythical matrixes of the Brazilian Amazon. The themes are distributed as follows: chapter 1 presents the exotic and the complexity in the distinction between reality and fiction in the travel reports, in light of practical alterity. Chapter 2 approaches the differences and contrasts between two foreigners and the Other , facing the reality observed. Chapter 3 reveals the encounter with the Other , the unknown, which resulted in a fictional transgeography . The theoretical parameters of support were based on the work by: Antonio Candido (1976), François Dosse (1993), Txyetan Todorov (1993), Julia Kristeva (1994), Telê Ancona Lopez (1996), Mikhail Bakhtin (2003), Emmanuel Lévinas (2005), among other authors. We prioritized the comparatist method of direct observation of the object on a fictional travel report, thus opening an equity relation in receiving the Other in its anonymity and, consequently, creating a rupture with the absolute thinking of science.